Complement Protein C1q Binds to Hyaluronic Acid in the Malignant Pleural Mesothelioma Microenvironment and Promotes Tumor Growth - Agostinis, Chiara; Vidergar, Romana; Belmonte, Beatrice; Mangogna, Alessandro; Amadio, Leonardo; Geri, Pietro; Borelli, Violetta; Zanconati, Fabrizio; Tedesco, Francesco; Confalonieri, Marco; Tripodo, Claudio; Kishore, Uday; et al. (Frontiers in Immunology, 2017)
C1q is the first recognition subcomponent of the complement classical pathway, which acts towards the clearance of pathogens and apoptotic cells. C1q is also known to modulate a range of functions of immune and non-immune cells, including their involvement in placental development and sensorial synaptic pruning. We have recently shown that C1q can promote tumour by encouraging their adhesion, migration and proliferation in addition to angiogenesis and metastasis. In this study, we have examined the role of C1q in the microenvironment of malignant pleuric mesothelioma (MPM), a rare form of cancer commonly associated with exposure to asbestos. We found that C1q was highly expressed in all MPM histotypes, particularly in epithelioid rather than in sarcomatoid histotype. C1q avidly bound high and low molecular weight hyaluronic acid via its globular domain. C1q bound to hyaluronic acid was able to induce adhesion and proliferation of mesothelioma cells via enhancement of ERK1/2, SAPK/JNK and p38 phosphorylation; however, it did not activate the complement cascade. Consistent with the modular organisation of the globular domain, we demonstrated that C1q may bind to hyaluronic acid through ghA module, whereas it may interact with human mesothelioma cells through the ghC. In conclusion, C1q highly expressed in MPM binds to hyaluronic acid and enhances the tumour growth promoting cell adhesion and proliferation. These data can help develop novel diagnostic markers and molecular targets for MPM.